Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1002/art.11425
|View full text |Cite
|
Sign up to set email alerts
|

Physiologic responses to hypoxia and implications for hypoxia‐inducible factors in the pathogenesis of rheumatoid arthritis

Abstract: This article describes the chemical modification of polyethylene terephthalate (PET) with a variety of compounds containing reactive glycidyl group(s). Four different modifiers, namely, diglycidyl ether of bisphenol‐A (DGEBA), N,N′‐bis[3(carbo‐2′,3′‐epoxypropoxy) phenyl] pyromellitimide (BGPM), triglycidyl glycerol (TGG), and triglycidyl isocyanurate (TGIC) were compared for their reactivity toward PET in the melt phase. It was found that the presence of tertiary nitrogen in the structure of the epoxide modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 142 publications
5
100
0
3
Order By: Relevance
“…Pathological conditions that damage local microvasculature may also result in hypoxia. Moreover, a recent study has also shown that infiltrating T cells in synovia of patients with rheumatoid arthritis contain high levels of HIF-1␣ (9), consistent with an important role for hypoxia in the inf lamed rheumatoid joint (10).…”
mentioning
confidence: 76%
“…Pathological conditions that damage local microvasculature may also result in hypoxia. Moreover, a recent study has also shown that infiltrating T cells in synovia of patients with rheumatoid arthritis contain high levels of HIF-1␣ (9), consistent with an important role for hypoxia in the inf lamed rheumatoid joint (10).…”
mentioning
confidence: 76%
“…Hypoxia occurs in cardiovascular, hematological, and pulmonary disorders, arthritic joints, atherosclerosis plaques, and ischemic wounds (28)(29)(30)(31). Previous reports showed that H/R induced the generation of a burst of reactive oxygen species, which could activate NF-kB (1,4).…”
Section: Discussionmentioning
confidence: 99%
“…This is underlined by our results in dermal fibroblasts, which identified hypoxia-induced molecules with a role in such diverse biologic processes as angiogenesis, proliferation, cellular metabolic pathways, and extracellular matrix accumulation. Cell culture studies performed under normoxic conditions at 20% oxygen clearly do not resemble the hypoxic environment present in vivo in SSc tissues (7). Thus, the interference with multiple hypoxia-driven pathways is overlooked with normoxic culture conditions and has not been taken into account in the majority of in vitro experiments in the past.…”
Section: Discussionmentioning
confidence: 99%